Evaluasi Antioksidan dan Antidiabetik Infusa Daun Karamunting (Rhodomyrtus tomentosa) pada Ikan Zebra (Danio rerio) - Susana Elya Sudradjat; Ika Rahayu (Universitas Muhammadiyah Purwokerto, 2022)
Background: Karamunting (Rhodomyrtus tomentosa) is a potential herbal plant that can be found in Kalimantan, Indonesia. This plant is widely used because of its benefits for health. Several studies show its ability as anti-inflammatory, anti-bacterial, anti-fungal, and anti-diabetic.Objective: This study aimed to evaluate the chemical content, antioxidant and anti-diabetic activity of the infusion of karamunting leaves.Methods: Liquid Chromatography-Mass Spectrometry (LCMS) was used for the phytochemical analysis of karamunting leaf infusion. Total phenolic content was calculated using Folin Ciocalteu's reagent. Antioxidant activity test using DPPH free radicals. An anti-diabetic activity test was performed using hyperglycemic-induced zebrafish.Results: There were 14 active compounds detected. There are three main fragments, namely Tectoridin, Engeletin, and Rhamnetin-3-O rhamnoside, in the infusion of karamunting leaves. The total phenolic content of the infusion of karamunting leaves was 288±5.94 g GAE/g. The antioxidant activity of karamunting leaf infusion was more potent than that of BHT (IC50 infusion 0.79±0.33 g/mL, BHT 13.5±2.5 g/mL). Karamunting leaf infusion has an ability that can be compared with metformin in lowering glucose levels in zebrafish blood.Conclusions: The main bioactive compounds in the infusion of karamunting leaves are Tectoridin, Engeletin, and Rhamnetin-3-O rhamnoside. The antioxidant activity of karamunting leaf infusion is powerful. Karamunting leaf infusion has the potential as an antihyperglycemic agent.